Challenges and Opportunities for Public Sector Administration in India - Saurandhri Panja (Journal of Management and Administration Provision, 2021)
In this paper, we analyze the difficulties and potentials of India's governmental administration. In India, the government is in charge of providing everything from public protection and healthcare to public schools and hospitals. However, bureaucratic inefficiency, corruption, political interference, and inadequate facilities are just some of the problems plaguing India's public sector. These problems have made it harder for government agencies to provide essential services to the public and damaged citizens' faith in those agencies. On the other hand, there are many ways in which Indian public administration can improve public service delivery, increase accountability and openness, and boost the country's economy. Recent studies have shown that e-governance, human resource development, and public-private partnerships can help India's public sector management overcome some of its current problems. The public sector administration in India needs to take a holistic and coordinated strategy that includes reforms in governance, infrastructure, and human resources in order to meet the challenges and take advantage of the opportunities. The government must also establish conditions that invite involvement from the private sector, push for technological advancement, and reward public accountability. Sustained effort and commitment from all parties involved are necessary to effectively handle the challenges and opportunities facing public sector administration in India. These kinds of reforms are necessary if India's public sector is ever going to meet the requirements and fulfill the hopes of its constituents.